Real and nominal political executive - Ra'ees, Wahabuddin (Cengage Learning, 2008)
The executive is the oldest of all branches of government. From the archaeological evidence in the Middle East, it is clear that the institution of executive (kingship) was well established over 5000 years ago. 1 It possesses great power and authority in any political system. The executive branch of government has remained at the center of power of the government since groups began to form government in society. It is "the apex of power in a political system at which policy is formed and through which it is executed."2 This chapter examines the nature and functions of political executive in Malaysia